2023
DOI: 10.3390/atmos14081217
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Change and Anthropogenic Activities on the Net Primary Productivity of Grassland in the Southeast Tibetan Plateau

Abstract: Climate change and anthropogenic activities have had a profound effect on the variation in grassland productivity in the Tibetan Plateau in recent decades. Quantifying the impacts of climatic and anthropogenic variables on grassland productivity is a necessary step in making the management policies of a sustainable grassland ecosystem. Net primary productivity (NPP) is an important part of the terrestrial carbon cycle and can be used to assess vegetation growth. Based on the Carnegie–Ames–Stanford Approach mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…The correlation between CPP and precipitation was mainly very strong positive in North Africa, which accounted for 89.90% of the area of North Africa and 25.36% of the overall area of Africa. Our study found that temperature and precipitation were the main climatic variables affecting CPP, which agreed well with previous studies [28][29][30][31]. Precipitation plays a stronger limiting role, suggesting that water resources are a major constraint to agricultural development, which is consistent with other studies [32][33][34][35][36][37].…”
Section: Spatial Analysis Of Constraints On Cppsupporting
confidence: 93%
“…The correlation between CPP and precipitation was mainly very strong positive in North Africa, which accounted for 89.90% of the area of North Africa and 25.36% of the overall area of Africa. Our study found that temperature and precipitation were the main climatic variables affecting CPP, which agreed well with previous studies [28][29][30][31]. Precipitation plays a stronger limiting role, suggesting that water resources are a major constraint to agricultural development, which is consistent with other studies [32][33][34][35][36][37].…”
Section: Spatial Analysis Of Constraints On Cppsupporting
confidence: 93%